2004
DOI: 10.3727/000000004783983837
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Angiogenesis by Autologous Bone Marrow Cell Implantation for Refractory Chronic Peripheral Arterial Disease Using Assessment of Neovascularization by 99mTc-Tetrofosmin (TF) Perfusion Scintigraphy

Abstract: We investigated efficacy and safety of implantation of autologous bone marrow mononuclear cells plus platelets, including endothelial progenitor cells (EPCs), for recovering refractory chronic peripheral arterial disease (PAD) using visual and quantitative analyses by Tc-tetrofosmin (TF) perfusion scintigraphy, and also investigated various quantitative assessments objectively. We performed 12 consecutive cases and 19 limbs and hands with severe chronic PAD that were almost Fontaine class IV (11/12 cases, abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 15 publications
0
55
0
Order By: Relevance
“…21 Although BMMNC or M-PBMNC intramuscular implantation has been used most often, both therapies have some risk: to collect about 500 mL of BMMNC, general anesthesia of about 4 h duration is necessary, and to collect PBMNC, about 3 h of apheresis with G-CSF treatment is required. [2][3][4][5][6][7][8][9][10][11][14][15][16][17][18] In a first cell-therapy trial, results of which were published in 2002, 22 ASO patients (44 limbs) were implanted with either BMMNC or PBMNC. 2 At 6 months after implantation, both therapies yielded improvements in terms of rest pain, ABI and transcutaneous oxygen pressure, but the clinical outcomes for BMMNC were significantly better than those for PBMNC.…”
Section: Introductionmentioning
confidence: 99%
“…21 Although BMMNC or M-PBMNC intramuscular implantation has been used most often, both therapies have some risk: to collect about 500 mL of BMMNC, general anesthesia of about 4 h duration is necessary, and to collect PBMNC, about 3 h of apheresis with G-CSF treatment is required. [2][3][4][5][6][7][8][9][10][11][14][15][16][17][18] In a first cell-therapy trial, results of which were published in 2002, 22 ASO patients (44 limbs) were implanted with either BMMNC or PBMNC. 2 At 6 months after implantation, both therapies yielded improvements in terms of rest pain, ABI and transcutaneous oxygen pressure, but the clinical outcomes for BMMNC were significantly better than those for PBMNC.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there was an increase in pain-free walking time (from 140±53 s to 451±74 s, p=0.034), ABI (from 0.65±0.08 to 0.73±0.07, p=0.055) and perfusion index (proximal area from 1.32±0.10 to 1.56±0.11, p=0.007) [56]. Perfusion scintigraphy could identify new collaterals after BMMNC transplantation [56]. The second work showed increased ABI (from 0.54±0.47 to 0.61±0.50, p<0.05) and TcPO 2 (28.4±15.4 mmHg to 37.1±24.4 mmHg) following BMNNC transplantation in 8 patients with PAD [57].…”
Section: Bmmncsmentioning
confidence: 98%
“…The beneficial effect of stem cell therapy has been evaluated by diverse outcomes. These include alleviation of pain [19,23,46,47,51,63,69], increased walking distance [19,20,23,47,51,53,55,56,63,68,69,77,78,80], improved ABI and TcPO 2 [19,20,23,47,53,55,56,50,63,68,69,73,74,77,78,80,81], but also hard endpoints, notably ulcer healing [19,20,47,49,63,69,74,78,80], quality of life [72] and limb salvage [20,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iba et al (2002) demonstrated that implantation of Peripheral blood mononuclear cells and platelets into ischemic limbs effectively induced collateral vessel formation using rat models, suggesting that this cell therapy is useful for therapeutic angiogenesis. Some reports indicated the efficacy and feasibility of the clinical use of cell therapy (TateishiYuyama et al, 2002;Kajiguchi et al, 2007;Matoba et al, 2008;Miyamoto et al, 2004). Therapeutic angiogenesis using cell transplantation (TACT) is a treatment strategy for nooption patients with CLI in Japan.…”
Section: Cell Therapies For Critical Limb Ischemiamentioning
confidence: 99%